Asymmetric enforcement of cooperation in a social dilemma - Nikos Nikiforakis; Hans-Theo Normann; Brian Wallace (Max Planck Institute for Research on Collective Goods, 2009)
We use a public-good experiment to analyze behavior in a decentralized asymmetric punishment institution. The institution is asymmetric in the sense that players differ in the effectiveness of their punishment. At the aggregate level, we observe remarkable similarities between outcomes in asymmetric and symmetric punishment institutions. Controlling for the average punishment effectiveness of the institutions, we find that asymmetric punishment institutions are as effective in fostering cooperation and as efficient as symmetric institutions. At the individual level, we find that players with higher punishment effectiveness contribute similar amounts to the public account, but have higher earnings and punish more than their weak counterparts.
Keywords: C92; D70; H41; 330; Öffentliches Gut; Soziale Gruppe; Strafe; Entscheidungstheorie; Test